The Communal Politics and Genesis of Pakistan: The Impact of British Rule on Communal Politics and the Genesis of Pakistan (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The British ruleand its policy of Divide and Rule bore special responsibility for the growth ofseparatist trends in Indian Nationalist politics and it could succeed onlybecause of internal social and political conditions. The British governmentused communalism to counter and weaken the growing national movement and thewelding of the Indian people into a nation. The drift from Nationalism to communalism was initiatedby Sir Syed Ahmad Khan when in August 1888 he set up the United IndianPatriotic Association with the avowed object of countering the Congresspropaganda and policy and to wean away people from the Congress. In 1893, hefounded the exclusively sectarian Muhammadan Anglo-Oriental Defence Associationof upper India to keep the Muslims aloof from political agitation andstrengthen British Rule in India.